2022
DOI: 10.3390/bacteria1010004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Genomic Characterization of Two Novel Bacteroidota Strains Asinibacterium spp. OR43 and OR53

Abstract: Asinibacterium spp. (Family Chitinophagaceae, Phylum Bacteroidota) are abundant in environments contaminated with heavy metals. We characterized the physiology and genome of two Asinibacterium species to elucidate their ability to survive and grow at ambient conditions in the uranium-contaminated environments. Both strains were able to grow at pH 4.5 or 50 mM nitrate under aerobic conditions and did not grow with alternative electron acceptors under anaerobic conditions. Asinibacterium sp. OR53 grew in medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Bacteroideota has been also reported as the predominant phylum among Antarctic lake bacteria and on the Tibetan plateau [ 37 , 38 ], while Pseudomonadota was also found as the second most abundant prokaryotic representative in the Earth’s major habitat types [ 39 , 40 , 41 ]. These heterotrophic bacteria have often been isolated, indeed, from a range of other extreme environments, such as deep seas, cold habitats, polar soil, and Antarctic ice cores [ 36 , 42 ]. The ecology of Asinibacterium still remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroideota has been also reported as the predominant phylum among Antarctic lake bacteria and on the Tibetan plateau [ 37 , 38 ], while Pseudomonadota was also found as the second most abundant prokaryotic representative in the Earth’s major habitat types [ 39 , 40 , 41 ]. These heterotrophic bacteria have often been isolated, indeed, from a range of other extreme environments, such as deep seas, cold habitats, polar soil, and Antarctic ice cores [ 36 , 42 ]. The ecology of Asinibacterium still remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Our genomic analysis revealed that the two strains have genes encoding a F1F0-type ATP synthase, which can export protons from their cytoplasm to cope with pH stress (Krulwich et al, 2011). In addition, genes encoding potas-sium transporters, which may be involved in pH homeostasis (i.e., both Kup-type low-affinity and Kdp-type high-affinity potassium transporters; Brzoska et al, 2022) were found in the genome of both strains (Table S3). Our results indicated that both strains will likely survive in pH 4 to 5 cloud water at night.…”
Section: Resultsmentioning
confidence: 99%